O significado de uma associação de usuários e familiares no tratamento e trajetória de vida de seus sócios - Noal, Martha Helena Oliveira (2014)
The Associação de Familiares, Amigos e Bipolares (AFAB) (Association of Family, Friends and Bipolars) is an extension project of the Federal University of Santa Maria/RS. AFAB was founded in 1997 as a nonprofit association that has as main objective to offer people with Bipolar Mood Disorder and their families a complementary therapeutic approach to the clinical treatment, which includes psychological, educational, cultural, family and social aspects with the aim of rehabilitating its participants psychosocially through comprehensive care. This qualitative study sought to understand the role of AFAB in the treatment and course of life of its members. Semi-structured interviews were performed with patients and their families and were analyzed using the method of categorical thematic content analysis. The benchmarks used were the pedagogical theories of Paulo Freire, the principles and guidelines of the National Humanization Policy, the model of health education through psychoeducation, and the prospects for empowerment of individuals. We analyzed three main issues of the interviews i) AFAB, history and meanings; ii) Bipolar Mood Disorder and its impact, and iii) Psychoeducation: health education and autonomy/citizenship. Based on these issues we inferred various categories that showed an influence of AFAB in improved self-esteem and quality of life of participants as well as an increase in their capacity for autonomy and empowerment. Furthermore, we observed an important role of AFAB in the learning process of its members, not only regarding health education to increase adherence to treatment, but also the development of skills that enabled a greater social impact and an improved worldview of their members.